A novel digital workflow to manufacture personalized three-dimensional-printed hollow surgical obturators after maxillectomy. Issue 9 (September 2018) - Kortes, J.; Dehnad, H.; Kotte, A.N.T.; Fennis, W.M.M.; Rosenberg, A.J.W.P.
Abstract: Partial or complete resection of the maxilla during tumour surgery causes oronasal defects, leading to oral-maxillofacial dysfunction, for which the surgical obturator (SO) is an important treatment option. Traditional manufacturing of SOs is complex, time-consuming, and often results in inadequate fit and function. This technical note describes a novel digital workflow to design and manufacture a three-dimensional (3D)-printed hollow SO. Registered computed tomography and magnetic resonance imaging images are used for gross tumour delineation. The produced RTStruct set is exported as a stereolitography (STL) file and merged with a 3D model of the dental status. Based on these merged files, a personalized and hollow digital SO design is created, and 3D printed. Due to the proper fit of the prefabricated SO, a soft silicone lining material can be used during surgery to adapt the prosthesis to the oronasal defect, instead of putty materials that are not suitable for this purpose. An STL file of this final SO is created during surgery, based on a scan of the relined SO. The digital workflow results in a SO weight reduction, an increased fit, an up-to-date digital SO copy, and overall easier clinical handling.